Hak-hak Komunitas Adat Terpencil dari Perspektif Hak Asasi Manusia - Hikmah, Mutiara (Indonesian Journal of International Law, 2009)
Indigenous People Right has had protection and part of human right issue. This issue is always discussed in national and international frame work. There are four points about Indigenous People Right which are discussed in this article. It will concern with the criteria of Indigenous People, the relation of Indigenous People with the land and its resources, right to self determination of Indigenous People and the protection of Indigenous People Right in national and international human right document.